Precise Regulation of miR-210 is Critical for the Cellular Homeostasis Maintenance and Transplantation Efficacy Enhancement of Mesenchymal Stem Cells in Acute Liver Failure Therapy. Issue 5 (May 2017) - Liu, Yingxia; Xiong, Yongjia; Xing, Feiyue; Gao, Hao; Wang, Xiaogang; He, Liumin; Ren, Chaoran; Liu, Lei; So, Kwok-Fai; Xiao, Jia
Stem cell transplantation is a promising clinical strategy to cure acute liver failure. However, a low cell survival ratio after transplantation significantly impairs its therapeutic efficacy. This is partly due to insufficient resistance of transplanted stem cells to severe oxidative and inflammatory stress at the injury sites. In the current study, we demonstrated that a small molecule zeaxanthin dipalmitate (ZD) could enhance the defensive abilities against adverse stresses of human adipose-derived mesenchymal stem cells (hADMSCs) in vitro and increase their therapeutic outcomes of acute liver failure after transplantation in vivo. Treatment with ZD dramatically improved cell survival and suppressed apoptosis, inflammation, and reactive oxygen species (ROS) production of hADMSCs through the PKC/Raf-1/MAPK/NF-κB pathway to maintain a reasonably high expression level of microRNA-210 (miR-210). The regulation loop between miR-210 and cellular/mitochondrial ROS production was found to be linked by the ROS inhibitor iron–sulfur cluster assembly proteins (ISCU). Pretreatment with ZD and stable knockdown of miR-210 significantly improved and impaired the stem cell transplantation efficacy through the alteration of hepatic cell expansion and injury amelioration, respectively. Vehicle treatment with ZD did not pose any adverse effect on cell homeostasis or healthy animal. In conclusion, elevating endogenous antioxidant level of hADMSCs with ZD significantly enhances their hepatic tissue-repairing capabilities. Maintenance of a physiological level of miR-210 is critical for hADMSC homeostasis.